1979
DOI: 10.1152/ajprenal.1979.236.4.f342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parathyroid hormone on electrolyte transport in the hamster nephron

Abstract: Recollection micropuncture and clearance studies were carried out on thyroparathyroidectomized hamsters to clarify the localization of the effects of parathyroid hormone (PTH) on renal electrolyte transport. The clearance data confirmed that PTH inhibits phosphate and enhances calcium and magnesium reabsorption. These effects appeared to result from actions of the hormone in several parts of the nephron. In the proximal tubule PTH did not affect H2O reabsorption but inhibited phosphate reabsorption ((TF/P)PO4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The site of PTH enhancement of magnesium transport has not been as extensively studied. Harris et al (26) demonstrated effects of PTH to enhance magensium reabsorption in the loop of Henle in the thyroparathyroidectomized hamster (26). Similarly, Quamme (6,8) demonstrated PTH-induced magnesium reabsorption when transport had been initially reduced by either hypermagnesemia or furosemide.…”
Section: Resultsmentioning
confidence: 99%
“…The site of PTH enhancement of magnesium transport has not been as extensively studied. Harris et al (26) demonstrated effects of PTH to enhance magensium reabsorption in the loop of Henle in the thyroparathyroidectomized hamster (26). Similarly, Quamme (6,8) demonstrated PTH-induced magnesium reabsorption when transport had been initially reduced by either hypermagnesemia or furosemide.…”
Section: Resultsmentioning
confidence: 99%
“…1,25(OH) 2 D 3 has been shown to stimulate intestinal absorption of Mg in some but not other studies, and so it may participate in ensuring the availability of sufficient Mg to provide for the body's needs (10,23). In addition, PTH stimulates renal tubular reabsorption of Mg in some species, especially the golden hamster (11). Even without PTH, peritubular (but not luminal) Mg as well as Ca inhibit the reabsorption of both Mg and Ca in the thick ascending limb (TAL) of Henle's loop in the kidney (5).…”
mentioning
confidence: 99%
“…In the proximal convoluted tubule, where Ca2+ transport is isotonic and generally associated with fluid and Na+ fluxes (1)(2)(3)(4), PTH has been shown to inhibit solute reabsorption isotonically (16)(17)(18)(19), or alternatively to have no effect on Ca2+ reabsorption (20,21). In the hamster, Harris et al (13) nephron is unclear. In some respects, the effect of PTH on proximal tubular solute reabsorption is similar to procedures which decrease peritubular Na+ concentrations or are presumed to increase cytosolic Ca2" (23).…”
mentioning
confidence: 99%